Pengembangan Aplikasi E-Assessment Skill Programming berbasis Web - Panyahuti Panyahuti; Yadi Yadi (Universitas Hamzanwadi, 2022)
In online learning, lecturers cannot assess students' programming abilities optimally. This is because the lecturer cannot see directly step by step in making program code. It is very possible that the program code sent by the student was not the result of his work. The purpose of this research is to develop a web-based assessment application using Jupyter Notebook. The development method uses Research and Development (RD) with a quantitative descriptive approach to several development processes, including needs analysis, data collection, application design, testing, and implementation. The data collection technique uses literature study, observation, and documentation with data analysis using the Aiken'V validation test. The results of the research are the development of E-Assessment applications that can be used by lecturers and students in the programming learning process with the results of application system validation 0.88, application output 0.85, user security 0.85, display design 0.84, and user convenience 0.83 so that the E-Assessment application is suitable for use in assessing students on programming skills.